Rotman lens combined with wide bandwidth antenna array for 60 GHz RFID applications. Issue 1 (4th August 2015) - Attaran, Ali; Rashidzadeh, Rashid; Muscedere, Roberto
Abstract : This paper presents a novel technique to design a Rotman lens feeding a wide bandwidth microstrip patch antenna array for 60 GHz radio frequency identification (RFID) applications. The proposed scheme supports both location positioning and increases the communication range through beam forming. The antenna array is designed using λ/4 microstrip transmission lines to support high gain, directivity, and bandwidth. The progressive phase delay using the Rotman lens is realized independently using transmission lines to reduce the complexity of the design and improve the performance parameters. The dummy ports are terminated by λ/4 radial stubs which eliminates the need for via holes and expensive connectors which reduces the fabrication costs.